2016
DOI: 10.1016/j.scitotenv.2015.09.132
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and fasting blood glucose: A longitudinal study in China

Abstract: Limited studies have examined the associations between air pollutants [particles with diameters of 10 μm or less (PM10), sulphur dioxide (SO2), and nitrogen dioxide (NO2)] and fasting blood glucose (FBG). We collected data for 27,685 participants who were followed during 2006 and 2008. Generalized Estimating Equation models were used to examine the effects of air pollutants on FBG while controlling for potential confounders. We found that increased exposure to NO2, SO2 and PM10 was significantly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
(55 reference statements)
4
32
1
Order By: Relevance
“…Studies of Eze et al, Liu et al, Wolf et al, and O’Donovan et al [17,58,59,60,61] are all cross-sectional studies and Liu et al [58] and both O’Donovan et al [61] and Wolf et al [59] had one and three years of follow-up, respectively. All of the studies found statistically significant results, as mentioned above, except for Chen et al [73], who found that exposure to PM 10 was associated with an increased level of FBG in the univariable analysis, whereas the results in the multipollutant model were not significant and Puett et al who found no strong evidence between PM and T2DM.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Studies of Eze et al, Liu et al, Wolf et al, and O’Donovan et al [17,58,59,60,61] are all cross-sectional studies and Liu et al [58] and both O’Donovan et al [61] and Wolf et al [59] had one and three years of follow-up, respectively. All of the studies found statistically significant results, as mentioned above, except for Chen et al [73], who found that exposure to PM 10 was associated with an increased level of FBG in the univariable analysis, whereas the results in the multipollutant model were not significant and Puett et al who found no strong evidence between PM and T2DM.…”
Section: Resultsmentioning
confidence: 84%
“…Diabetes status can be measured directly from biomarkers [68], such as fasting blood glucose (FBG), but also because insulin resistance (IR) and inflammation are important hallmarks of T2DM, biomarkers of inflammation, such as C-reactive protein (CRP), are also relevant. Most of the studies in this review used questionnaires and interviews, that collected information on treatment, blood glucose measurements, insulin, leptin, HbA1c, and CRP levels [69,70,71,72], but some studies carried out only blood tests of the above biomarkers [17,58,73], or used both methods [24,59,74]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations